NILAI-NILAI PENDIDIKAN ISLAM DALAM TRADISI PAKANDEANA ANA ANA MAELU DI KECAMATAN KOKALUKUNA - Haeria (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2022)
This research aims to look at the values of Islamic education in the traditions of society, namely pandeana ana anan maelu which means feeding orphans. This research uses a qualitative method with a descriptive approach. The method used shows that the tradition of glorifying orphans is a tradition that has been absorbed from Islamic teachings into the culture of society and the process of absorption follows the quality of education possessed by individuals in society which will later be practiced as a form of expression of gratitude to Allah SWT for their advantages. assets or excess income entrusted to individuals or individuals who hope for Allah's blessing by glorifying orphans